PENGARUH LAYANAN BIMBINGAN KELOMPOK TERHADAP KESIAPAN KEMBALI KE MASYARAKAT BAGI WARGA BINAAN ANAK KASUS NON NARKOBA DI LAPAS KELAS II B ANAK PEKANBARU - Muhammad Zakri; Zulfaan Saam; Raja Arlizon (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This study aims to determine the effect of group guidance services on the readiness to return to the community for the child assisted children non-drug cases in pekanbaru children’s correctional institution. The research method used is pre experimental method using The One Group Pretest-Posttest Design pattern. The method used in group guidance is the technique of giving information. The subjects of this research is 7 children inmates non drug cases. This research was conducted by providing group guidance services for 5 meetings. The analysis used is Wilcoxon test and Rank Spearman test. The results showed that there was a difference in the level of readiness to return to the community before it was given group counseling service (Asymp sign was obtained at 0.018 where 0.018 <0.05 = significant). And there is also a significant effect of group counseling services on the readiness to return to the community (obtained Asymp Sign at 0.034 where 0.034 <0.05 = significant).Keyword : The Readiness to Return to the Community, Group Guidance, Children Inmates